Success Story of Rishiwat Farmers Producer Company Ltd: Empowering Small and Marginal Farmers - S.K. Deshmukh (Journal of Agricultural Extension Management, 2022)
Small and Marginal farmers do not have the economic strength to adopt production technologies, services, and marketing including value addition. The formation of a Farmer Producer Company (FPC) will enable farmers to have collective strength for better access to quality input, technology, credit, better marketing access and enhance bargaining power. This is a case study of Rishiwat Farmers Producers Company Ltd (RFPCL). This case presents the rationale behind establishing RFPCL, challenges faced by farmers and efforts by RFPCL in overcoming these their initiatives, impact and sustainability plan.